Точність та похибка визначення місцеположення рухомого залізничного транспорту і вплив зовнішніх умов - Аль Равашдех Лейт Ахмед Мустафа (ХНУРЕ, 2019)
The urgency of the chosen topic is determined by the need for the development and application of systems for locating mobile rail transport for the purpose of managing mobile objects of railway transport. Thepurposeoftheworkistoformulateandsolvetheproblemofimprovingthetransportationprocessinordertoincreasetheefficiencyofitsoperationbymeansofthesystemoflocatingtherailwayrollingstock.